(untitled) (Rajshahi University Journal of Science and Engineering, 2016)
In biofuel technology from microalgae, the main optimal factors for microalgae cultivations are light, CO2 and temperature. As microalgae are photosynthetic microorganisms thus they convert sunlight, water and CO2 to algal biomass. We consider a two phase flow for CO2 and Microalgae suspension to understand fluid dynamics phenomena after injecting CO2 gas inside a tubular Photobioreactor (PBR).The growth rate of the microalgae cell is taken as a function of available sun light at Chittagong University of Engineering & Technology (CUET) in our study. A 20.94m long and 0.025m tubular PBR is considered for the simulation. To observe the microalgae cell growth, we selected the 21st June for a bright sunny and the longest day of a year. From the simulation after day seven we observed a very slow growth for the microalgae culture. It is noted that the growth related to concentration of microalgae is increased by day length with respect to continuous sunlight. A small fluctuation of shear rate around Uloop area is also found in our simulation which may be caused to reduce the volumetric production due to cell fragility. From the velocity profile we found that, the velocity is generally higher in the middle of the tube gives a parabolic shape of the suspension flow.